Synthesis of [1,4]Oxathiepino[5,6-b]quinolines via Base-Mediated Intramolecular Hydroalkoxylation - Tonekaboni, Maryam-Sadat; Tanbakouchian, Zahra; Majedi, Soma; Shiri, Morteza (SynOpen, 2022)
A base-mediated intramolecular hydroalkoxylation that was used to prepare a series of seven-membered S,O-heterocycles is described. 2-Thiopropargyl-3-hydroxymethyl quinolines were prepared starting from 2-mercaptoquinoline-3-carbaldehydes, via S-propargylation and reduction of a formyl group. Interestingly, 2-mercaptopropargyl-3-hydroxymethyl quinolines were converted into the corresponding oxathiepinoquinolines in the presence of t-BuOK. It is proposed that the S-propargyl moiety, in the presence of base, is converted into its allenyl isomer; subsequent addition of a hydroxyl group to the terminal double bond yields the 3-methyl-5H-[1,4]oxathiepino[5,6-b]quinoline in good to high yield. Notably, the procedure is adaptable to the conversion of N-propargyl indole-2-methanol into the corresponding intramolecular hydroalkoxylation product.
Keywords: quinoline; 2-chloroquinoline-3-carbaldehyde; intramolecular reactions; hydroalkoxylation; base-mediated cyclization; allenes